2005
DOI: 10.1248/bpb.28.886
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific mRNA Expression Profiles of Human Toll-Like Receptors and Related Genes

Abstract: The mRNA expression levels of 10 toll-like receptors (TLRs) and 21 related genes in total RNA from pooled specimens of fetal human tissues (brain and liver), from single and pooled specimens of various adult human tissues (adrenal gland, brain, heart, kidney, liver, lung, placenta, prostate, salivary gland, skeletal muscle, small intestine, spinal cord, spleen, testis, thymus, thyroid gland, trachea, and uterus), and from two cell lines (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
288
3
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(316 citation statements)
references
References 21 publications
22
288
3
3
Order By: Relevance
“…On further analysis, we found that in parallel to studies in human tissues, the endogenous expression of these genes in mock-injected animals was significantly higher in the spleen than in the liver, and in most cases was also significantly higher compared with lung tissue. 66 It is possible that because these genes are already expressed at high levels in this tissue, their induction by systemically injected Ads is either less significant, or limited to only a low percentage of spleen cells, and thus not detectable by the methods utilized in this study.…”
Section: Had3 and Sad23 Activate Complement In Human Serummentioning
confidence: 97%
“…On further analysis, we found that in parallel to studies in human tissues, the endogenous expression of these genes in mock-injected animals was significantly higher in the spleen than in the liver, and in most cases was also significantly higher compared with lung tissue. 66 It is possible that because these genes are already expressed at high levels in this tissue, their induction by systemically injected Ads is either less significant, or limited to only a low percentage of spleen cells, and thus not detectable by the methods utilized in this study.…”
Section: Had3 and Sad23 Activate Complement In Human Serummentioning
confidence: 97%
“…By contrast, cytokine response to TLR ligands by primary cultures of MGT organs still has not been fully studied. Nishimura & Naito (2005) showed the presence of TLR1-TLR10 mRNA in human testes by real-time PCR. In addition, Palladino et al (2007) showed TLR1-9 mRNA and protein in testes, epididymis and vas deferens.…”
Section: Discussionmentioning
confidence: 98%
“…TLR 5 toll-like receptor; PBS 5 phosphate-buffered saline; PRV 5 pseudorabies virus. and accessory glands of the man and male mice (Nishimura and Naito, 2005). The stimulation of TLR by virus leads to expression and release of pro-inflammatory cytokines (Zhang et al, 2007) and ultimately results in inflammation (Unterholzner and Bowie, 2008).…”
Section: Discussionmentioning
confidence: 99%